Factors Influencing the Implementation of Screening and Brief Interventions for Alcohol Use in Primary Care Practices: A Systematic Review Protocol - Rosário, Frederico; Santos, Maria Inês; Angus, Kathryn; Pas, Leo; Fitzgerald, Niamh (Acta Médica Portuguesa, 2018)
Introduction: Alcohol is a leading risk factor contributing to the global burden of disease. National and international agencies recommend evidence-based screening and brief interventions in primary care settings in order to reduce alcohol consumption. However, the majority of primary care professionals do not routinely deliver such interventions. Objective: To identify factors influencing general practitioners/family physicians’ and primary care nurses’ routine delivery of alcohol screening and brief intervention in adults. Material and Methods: A systematic literature search will be carried out in the following electronic databases: Medline, CINAHL, CENTRAL, and PsycINFO. Two authors will independently abstract data and assess study quality using the NIH National Heart, Lung, and Blood Institute quality assessment tools for quantitative studies, and the CASP checklist for qualitative studies. A narrative synthesis of the findings will be provided, structured around the barriers and facilitators identified. Identified barriers and facilitators will be further analysed using the Behavioural Change Wheel/Theoretical Domains Framework. Discussion: This review will describe the barriers to, and facilitators for, the implementation of alcohol screening and brief interventions by general practitioners/family physicians and nurses at primary care practices. By mapping the barriers and facilitators to the domains of the Behavioural Change Wheel/Theoretical Domains Framework, this review will also provide implementation researchers with a useful tool for selecting promising practitioner-oriented behavioural interventions for improving alcohol screening and brief intervention delivery in primary care. Conclusion: This review will provide important information for implementing alcohol screening and brief intervention in primary health care. Systematic Review Registration: PROSPERO CRD42016052681